Opposite effects of catalase and MnSOD ectopic expression on stress induced defects and mortality in the desmin deficient cardiomyopathy model - Rapti, Kleopatra (Free radical biology and medicine, 2017)
Oxidative stress has been linked strongly to cell death and cardiac remodeling processes, all hallmarks of heart failure. Mice deficient for desmin (des-/-), the major muscle specific intermediate filament protein, develop dilated cardiomyopathy and heart failure characterized by mitochondrial defects and cardiomyocyte death. The cellular and biochemical alterations in the hearts of these mice strongly suggest that oxidative stress is one of the mechanisms contributing to the pathogenesis of the phenotype. Recently, we showed that indeed the desmin deficient cardiomyocytes are under increased oxidative stress. In order to verify these findings in vivo, we generated transgenic animals overexpressing SOD2 (MnSOD) and/or catalase in the heart and crossed them with des-/- mice, thus allowing us to evaluate the contribution of oxidative injury in inherited cardiomyopathies, as well as the therapeutic potential of antioxidant strategies. Moderate MnSOD and/or catalase overexpression in des-/- hearts leads to a marked decrease in intracellular reactive oxygen species (ROS), ameliorates mitochondrial and other ultrastructural defects, minimizes myocardial degeneration and leads to a significant improvement of cardiac function. Importantly, catalase overexpression increased the 50% survival rate of des-/- mice in an obligatory exercise to 100%. In contrast, MnSOD overexpression enhanced the lethality of des-/- mice, underscoring the importance of a fine balanced cellular redox status. Overall, the present study supports the contribution of oxidative stress in the development of des-/- cardiomyopathy and points to a well-considered antioxidant treatment as therapeutic for cardiomyopathies.
Gesehen am 07.06.2018